Characterisation of the Polyphenol Content in the Kiwifruit (Actinidia deliciosa) Exocarp for the Calibration of a Fruit‐sorting Optical Sensor. Issue 5 (28th May 2013) - Pinelli, Patrizia; Romani, Annalisa; Fierini, Elisa; Remorini, Damiano; Agati, Giovanni; de, Victor; Comte, Gilles; Santos‐Buelga, Celestino
ABSTRACT Introduction Kiwifruit contains high amounts of anti‐oxidants beneficial to health. Its quality is influenced by ripening time, genotype, cultivation techniques, climate and storage conditions after harvest. Objective The aim of the present study was to characterise the phenolic content by HPLC methods and to evaluate the performance of a portable optical sensor (Multiplex 3), for in vivo non‐destructive phenolic compound assessment in kiwifruits. Methods Kiwifruits peel extracts were characterised by reverse‐phase (RP) HPLC with diode‐array detector (DAD) and electrospray ionisation (ESI) with MS using the Zorbax SB‐Aq. column from Agilent. The fluorimetric sensor method is based on the screening of fruit chlorophyll fluorescence excitation and allows the UV absorbance of intact fruit skin to be measured. The flavonol index, FLAV, was calculated as log(FRFR/FRFUV), where FRFR and FRFUV are the chlorophyll fluorescence excited with red and UV light. Results Hydroxycinnamic acids, procyanidins, and quercetin glycosides were the main polyphenol classes detected by HPLC–DAD–ESI/MS in the kiwifruit skin. A good linear regression (R2 = 0.88) was found between the fluorimetric sensor FLAV index and flavonol chromatographic analysis of the fruits. The FLAV index was able to detect the higher content of flavonols in sun‐exposed fruits with respect to mid‐shaded and shaded ones in accordance with the destructive analysis. Conclusion The fluorimetric sensor represents a rapid and non‐invasive tool to: (i) monitor the flavonol accumulation in kiwifruit and to assess its quality concerning the healthy anti‐oxidant properties; (ii) evaluate the effect of environmental and agronomical factors related to the fruit quality; and (iii) select fruits with the largest flavonol content, and consequently less susceptible to pathogen attack, in order to improve their storage durability. Copyright © 2013 John Wiley & Sons, Ltd.